Correlation Between Neutrophil to Lymphocyte Ratio and Myocardial Injury in Population Exposed to High Altitude - Siyi He (Frontiers Media S.A., 2021)
Objective: Myocardial injury is a severe complication in population exposed to high altitude. As a new biomarker for inflammatory response, neutrophil to lymphocyte ratio (NLR) has been widely used to predict the prognosis of various diseases. In this study, we intend to explore the risk factors for myocardial injury at high altitude and examine the relationship between NLR level and development of myocardial injury.Methods: Consecutive patients admitted to a secondary general hospital at high altitude from June 2019 to May 2020 were selected into this retrospective study. Clinical and biochemical data were collected. According to the results of lactate dehydrogenase (LDH), creatine kinase (CK), creatine kinase isoenzymes (CK-MB), and aspartate amino transferase (AST), patients were divided into myocardial injury group and normal group.Results: A total of 476 patients were enrolled in this study. Myocardial injury occurred in 158 patients (33.2%). We found that altitude, NLR, hemoglobin, total bilirubin, total cholesterol, and lipoprotein A in myocardial injury group were significantly higher than that in normal group (P < 0.05), while platelet count in myocardial injury group was significantly lower than that in normal group (P < 0.05). Logistic multivariate regression analysis revealed that there was an independent relationship between myocardial injury and smoke, NLR, hemoglobin (P < 0.05). By using Spearman correlation analysis, NLR was proved to have a significant positive correlation with LDH, CK, and CK-MB (P < 0.05) instead of AST. A receiver operating characteristic (ROC) curve was drawn to demonstrate that NLR could significantly predict the occurrence of myocardial injury with an area under the curve (AUC) of 0.594 (95% CI: 0.537–0.650, P < 0.05), and the level of 2.967 (sensitivity = 38.0%, specificity = 83.6%) was optimal cutoff value.Conclusion: The incidence of myocardial injury is high in population at high altitude. Smoke, hemoglobin, and NLR are independent factors related to myocardial injury. As a convenient and efficient marker, NLR is found to be closely associated with myocardial enzymes and have a predict role in the occurrence of myocardial injury. This study will provide a theoretical basis on NLR for the early diagnosis of myocardial injury at high altitude.